Tool Wear Assessment During Machining of Inconel 718. (2017) - Xavior, M. Anthony; Manohar, M.; Jeyapandiarajan, P.; Madhukar, Patil Mahesh
Abstract: Machining of superalloy Inconel 718 would have established some issues like, inability of the tool materials to sustain for a longer duration due to the work hardening effect and very high cutting forces causes metallurgical damage on the work pieces. This research paper focuses on the tool life issues of different tool materials associated with the turning of Inconel 718 under different cutting conditions. Further, it is significant to identify the parameters that cause the machining characteristics, in particular the flank wear and to understand the relationship they have with the different controllable parameters. Turning experiments on Inconel – 718 were investigated under different cutting conditions using three controllable parameters namely feed rate, cutting speed and depth of cut. Three different cutting tools such as PVD TiAlN coated carbide inserts, Al2 O3 – TiC Ceramic and cBN inserts with constant tool geometry were used for all experimental trials. The flank wear occurred on the inserts during every trail are measured and recorded using CARL ZIESS Optical Microscope having 50 X to 1500 X magnification, equipped with Clemex Vision Professional Edition Image Analysis Software. Scanning Electron Microscope (SEM) observations were made to understand the wear pattern encountered by different tool materials. Analysis of Variance (ANOVA) was performed to understand the percentage influence of all the cutting parameters on the flank wear.